Presentation skills for scientists : a practical guide - Zanders, Edward D.; MacLeod, Lindsay (Cambridge : Cambridge University Press, 2010)
'Scientists are rarely given formal training in presentation skills and yet are often called upon to present the results of their research. This book provides a practical guide to the creation and delivery of scientific presentations, whatever the topic. Its practical'how-to' style leaves discussion of the background psychology of public speaking to others and focuses instead on the issues that are of immediate concern to the busy scientist. The text covers all of the important aspects of scientific presentations, ranging from audience awareness to handling questions. Links are included throughout the text to the accompanying DVD, which contains annotated video clips of speakers delivering a talk and demonstrates the common problems found with many presenters, as well as the exercises designed to overcome them. Image files of different slide layouts, colour schemes and font styles demonstrate the design issues that one must consider when creating visual material'--Provided by publisher.
'A scientific presentation is normally a formal communication of information to an audience at a conference, seminar or laboratory meeting. The majority of talks describe the background and design of experiments to increase knowledge of a particular scientific phenomenon. Then the results of these experiments are delivered, as well as the conclusions that can be drawn from them. The conclusions drawn from these experiments and the data that support them are almost always the most important pieces of information that can be communicated to an audience of fellow scientists. Presentations are therefore a showcase for your work, or that of your institution. How well you deliver scientific information depends on a number of factors; these include control of nerves and voice, as well as creating visual media that convey information clearly in as short a time as possible'--Provided by publisher.
Audience -- Planning the talk -- Selection and assembly of visual material -- Controlling nerves -- Voice -- Delivery -- Science and the English language -- Handling questions -- How did it go?
Book is a accompained by one CD, entittled' Presentation skills for scientists : a practical guide' bearing the same call number and available at Bahagian Koleksi Media
Includes bibliographical references and index.
Keywords: Communication in science; Public speaking; Scientists -- Vocational guidance